Genetically Encoded Libraries of Nonstandard Peptides - Kawakami, Takashi; Murakami, Hiroshi (Journal of Nucleic Acids, 2012)
The presence of a nonproteinogenic moiety in a nonstandard peptide often improves the biological properties of the peptide. Non-standard peptide libraries are therefore used to obtain valuable molecules for biological, therapeutic, and diagnostic applications. Highly diverse non-standard peptide libraries can be generated by chemically or enzymatically modifying standard peptide libraries synthesized by the ribosomal machinery, using posttranslational modifications. Alternatively, strategies for encoding non-proteinogenic amino acids into the genetic code have been developed for the direct ribosomal synthesis of non-standard peptide libraries. In the strategies for genetic code expansion, non-proteinogenic amino acids are assigned to the nonsense codons or 4-base codons in order to add these amino acids to the universal genetic code. In contrast, in the strategies for genetic code reprogramming, some proteinogenic amino acids are erased from the genetic code and non-proteinogenic amino acids are reassigned to the blank codons. Here, we discuss the generation of genetically encoded non-standard peptide libraries using these strategies and also review recent applications of these libraries to the selection of functional non-standard peptides.